HIGH FREQUENCY PERFORMANCE MEASURING OF ETHERNET CABLES - Ziļs, Arturs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Article contains information about Ethernet Network cable high frequency performance categories. What is main characteristics for Network cable performance. Information from this article can help choose which category is necessary for user and can help save sources.